Extracellular Matrix–Mediated Maturation of Human Pluripotent Stem Cell–Derived Cardiac Monolayer Structure and Electrophysiological Function. (April 2016) - Herron, Todd J.; Rocha, Andre Monteiro Da; Campbell, Katherine F.; Ponce-Balbuena, Daniela; Willis, B. Cicero; Guerrero-Serna, Guadalupe; Liu, Qinghua; Klos, Matt; Musa, Hassan; Zarzoso, Manuel; Bizy, Alexandra; Furness, Jamie; et al.
Abstract : Background—: Human pluripotent stem cell–derived cardiomyocytes (hPSC-CMs) monolayers generated to date display an immature embryonic-like functional and structural phenotype that limits their utility for research and cardiac regeneration. In particular, the electrophysiological function of hPSC-CM monolayers and bioengineered constructs used to date are characterized by slow electric impulse propagation velocity and immature action potential profiles. Methods and Results—: Here, we have identified an optimal extracellular matrix for significant electrophysiological and structural maturation of hPSC-CM monolayers. hPSC-CM plated in the optimal extracellular matrix combination have impulse propagation velocities ≈2× faster than previously reported (43.6±7.0 cm/s; n=9) and have mature cardiomyocyte action potential profiles, including hyperpolarized diastolic potential and rapid action potential upstroke velocity (146.5±17.7 V/s; n=5 monolayers). In addition, the optimal extracellular matrix promoted hypertrophic growth of cardiomyocytes and the expression of key mature sarcolemmal ( SCN5A, Kir2.1, and connexin43) and myofilament markers (cardiac troponin I). The maturation process reported here relies on activation of integrin signaling pathways: neutralization of β1 integrin receptors via blocking antibodies and pharmacological blockade of focal adhesion kinase activation prevented structural maturation. Conclusions—: Maturation of human stem cell–derived cardiomyocyte monolayers is achieved in a 1-week period by plating cardiomyocytes on PDMS (polydimethylsiloxane) coverslips rather than on conventional 2-dimensional cell culture formats, such as glass coverslips or plastic dishes. Activation of integrin signaling and focal adhesion kinase is essential for significant maturation of human cardiac monolayers. Abstract : Supplemental Digital Content is available in the text.